An EPQ model for deteriorating items with variable demand rate and allowable shortages. (2018) - Khurana, Deepa; Tayal, Shilpy; Singh, S.R.
The fundamental assumption of an economic order quantity (EOQ) model is that 100% of items in an ordered lot are perfect. This assumption is not always pertinent for production processes because of process deterioration or other factors. This is an economic production quantity model for deteriorating items. To fulfil the market demands and expectations, the production rate is taken as a function of demand rate. The demand and deterioration of the products are time dependent function. Shortages are allowed and partially backlogged. The backlogging phenomenon in the literature is often modelled using backordering and lost sale costs. The backlogging option gets used only when it is economic to do so. The inventory policy proposed here considers the optimal production run time, production quantity and shortage period such that the total average cost can be minimised. Numerical examples are provided to illustrate and sensitivity analyses of optimal solutions are given for the proposed inventory model.